Etiology and Management of Dyslipidemia in Patients With Cancer - de Jesus, Mikhail; Mohammed, Turab; Singh, Meghana; Tiu, John G.; Kim, Agnes S. (Frontiers in Cardiovascular Medicine, 2022)
Patients with cancer are now living longer than ever before due to the growth and expansion of highly effective antineoplastic therapies. Many of these patients face additional health challenges, of which cardiovascular disease (CVD) is the leading contributor to morbidity and mortality. CVD and cancer share common biological mechanisms and risk factors, including lipid abnormalities. A better understanding of the relationship between lipid metabolism and cancer can reveal strategies for cancer prevention and CVD risk reduction. Several anticancer treatments adversely affect lipid levels, increasing triglycerides and/or LDL-cholesterol. The traditional CVD risk assessment tools do not include cancer-specific parameters and may underestimate the true long-term CVD risk in this patient population. Statins are the mainstay of therapy in both primary and secondary CVD prevention. The role of non-statin therapies, including ezetimibe, PCSK9 inhibitors, bempedoic acid and icosapent ethyl in the management of lipid disorders in patients with cancer remains largely unknown. A contemporary cancer patient needs a personalized comprehensive cardiovascular assessment, management of lipid abnormalities, and prevention of late CVD to achieve optimal overall outcomes.